Experimental study on internal precast beam–column ultra-high-performance concrete connection and shear capacity of its joint. (December 2021) - Ma, Fudong; Deng, Mingke; Yang, Yong
Abstract: Precast reinforced concrete structures are increasingly being studied and adopted for their potential advantages. In this study, we tested five precast beam–column connections whose regular shape beams and columns were connected with lap-spliced steel bars in ultra-high-performance concrete (UHPC). A monolithic beam–column connection as a control specimen was also tested under reverse cyclic loading. The results showed that the application of lap-spliced steel bars in UHPC is feasible for connecting the beam and column in the joint. It is recommended that the minimum straight bar lap length in UHPC can be determined as 15 d b ( d b is the bar diameter), and the minimum hooked bar lap length was determined as 11 d b (with a straight extension length of 8 d b, inside bend diameter of 4 d b, and tail extension length of 5 d b ). UHPC significantly enhanced the shear capacity of the joint owing to its high shear strength. The increases in the fiber volume fraction and stirrup volume ratio enhanced the damage-resistance property of the joint, which is beneficial for the development of beam-end plastic hinges. Therefore, the ductility of the beam–column connection can be further increased. The increase in axial load enhanced the shear capacity. To design a "strong joint, " a theoretical strut-and-tie model was proposed based on Mohr–Coulomb theory applied to the joint core to accurately calculate the UHPC joint shear capacity. Highlights: The application of LS-UHPC is feasible to connect the beam and column in joint. UHPC significantly enhanced the shear capacity of joint. The increases of fibers and stirrups enhanced the damage-resistance property of UHPC joint. A theoretical strut-and-tie model was proposed to calculate the UHPC joint shear capacity.